'Life finds a way': mapping a post-positivist marxian science. Issue 2 (3rd April 2018) - Kingsmith,; von Bargen,
Abstract : ABSTRACT The rise of populist ethnonationalist movements – and the breakdown of global liberal cosmopolitanism – caught most political analysts and theorists by surprise. This article takes this failure of political expertise as a challenge to reconsider radical Left approaches in making sense of political turmoil, economic crises, and class. Specifically, this article examines two key Marxian concepts, class and crisis, in relation to chaos. The authors argue that political expertise fails because the infinite velocities of chaos cannot be indefinitely contained categorically for three reasons: (1) because chaos understood as unpredictability is a property inherent to reality; (2) because there is no Archimedean point from outside of being in the world to objectively observe the world; and (3) because observing the world is always linked to intervening in it, a process through which the observer and the observed are both changed. To this end, the authors seek to augment crisis and class as concepts with a capacity to capture the nonlinear ways in which existing class struggle has developed across space and over time. To capture these complexities, the authors develop dadascience, a scientific apparatus of constant abandonment designed to account for determinations in relation to indeterminacy.